A sit-ski design aimed at controlling centre of mass and inertia - Langeliera, E.; Martela, S.; Millota, A.; Lessarda, J.-L.; Smeestersa, C.; Rancourta, D. (Journal of Sports Sciences, 2013)
This article introduces a sit-ski developed for the Canadian Alpine Ski Team in view of the Vancouver 2010 Paralympic games. The design is predominantly based on controlling the mass distribution of the sit-ski, a critical factor in skiing performance and control. Both the antero-posterior location of the centre of mass and the sit-ski moment of inertia were addressed in our design.